Study of clinical patterns and frequency of cutaneous manifestations in the elderly - Paliwal, Gaurav; Saxena, Kshitij; Koti, Venkatarao; Shukla, Priyanka; Dutt, Shobhit; Usmani, Shams Zia; Jain, Chandni; Khalid, Ayesha (International Journal of Research in Dermatology, 2019)
Background: Cutaneous manifestations are common in elderly. The elderly population is composed of persons over 60 years of age and very few studies are available on the dermatologic diseases in this group. This study was done to study the clinical pattern and frequency of cutaneous manifestations in the elderly. Methods: A cross sectional observational study was conducted on 540 patients, aged 60 years and above, who attended the out-patient department and admitted as inpatients having cutaneous manifestations were included, in the department of dermatology Era’s Lucknow Medical College And Hospital, Lucknow. A detailed history was taken regarding the onset and duration of cutaneous manifestations. Thorough dermatological examination was carried out on all study patients. Relevant investigations which included haemogram, biochemical tests and a skin biopsy were performed, wherever needed. Skin changes in all the patients were recorded and were classified into physiological and pathological changes. Data were entered in an Excel sheet and were analyzed using descriptive statistics. Results: Out of 540 patients studied, 55.7% were males and 44.3% were females. Pruritus was the single most common complaint elicited (90.6%). Among the physiological changes, wrinkling was the commonest (80.9%). Among the pathological changes skin tumours, eczemas, infections were the common findings. Conclusions: The geriatric dermatoses are different in different populations, as there is significant number of geriatric population, the increased emphasis on geriatric medicine is inevitable. This present study helps in providing greater understanding of pattern of geriatric dermatoses that aids in early diagnosis and management.